2013
DOI: 10.1038/jhh.2013.32
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of patients with resistant hypertension: the RESIST-POL study

Abstract: Recent studies indicate that resistant hypertension (RHTN) is present in about 12% of the treated hypertensive population. However, patients with true RHTN (confirmed out of the office) have not been widely studied. We prospectively studied 204 patients (123 male, 81 female, mean age 48.4 years, range 19-65 years) with truly RHTN (ambulatory daytime mean blood pressure >135/85 mm  Hg). We evaluated the frequency of obstructive sleep apnea (OSA), renal artery stenosis (RAS), primary aldosteronism (PA) and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
3
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 38 publications
2
68
3
8
Order By: Relevance
“…The study was approved by the Ethics Committee of the National Institute of Cardiology, Warsaw and informed written consent was obtained from each patient [6].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was approved by the Ethics Committee of the National Institute of Cardiology, Warsaw and informed written consent was obtained from each patient [6].…”
Section: Methodsmentioning
confidence: 99%
“…PA also overlapped with MS and OSA [6]. Because the coexistence of PA and OSA in patients with resistant hypertension has been reported only by a few authors, we analysed the relationship between PA and OSA, metabolic abnormalities and cardiac structure in patients with true resistant hypertension enrolled in the RESIST-POL Study [6,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much more rare causes include Cushing's syndrome, pheochromocytoma, hyperparathyroidism, coarctation of the aorta, intracranial tumours. Referral and specific treatment of these diseases can improve blood pressure control and long-term prognosis [2,4].…”
mentioning
confidence: 99%
“…The development of true RAH is promoted by specific, potentially reversible causes of secondary hypertension, such as renal artery stenosis and pheochromocytoma. It is shown that primary aldosteronism is much more common in hypertension than in the general population, reaching 20% at the RAH [1,2,4].…”
mentioning
confidence: 99%